Case study on strengthening methods for progressive collapse resistance of RC flat slab buildings. (February 2021) - Garg, Suyash; Agrawal, Vinay; Nagar, Ravindra
Abstract: The progressive collapse of buildings may result in major financial losses and fatalities, so reducing the chances of such occurrences is of paramount importance. Due to the absence of beams for redistribution of gravity loads that were initially resisted by the missing column, flat slab buildings are more prone to progressive collapse than moment frame buildings. Thus, flat slab buildings should necessarily be assessed for progressive collapse and strengthened accordingly in order to avoid the likelihood of progressive collapse. This study evaluates the efficacy of three different strengthening methods for reducing the potential for progressive collapse of a validated 3-bay by 3-bay 4-storey flat slab building simulation model, subject to alternate, simultaneous and sequential removal of columns in the first storey. Corner, edge and interior columns of each building model are statically and instantaneously removed and the static and dynamic response of the building is compared for different removal sequences. The three strengthening strategies investigated are the addition of perimeter beams, the addition of shear walls and the addition of both perimeter beams and shear walls. The results are evaluated in terms of the vertical displacements at the top of the removed columns and the DCR of the sectional forces of critical adjacent columns, for which the acceptance criteria provided for DCR by the GSA is used to assess the vulnerability of the studied building to progressive collapse. The results show that perimeter beam, shear wall and combination of both perimeter beam and shear wall improve the progressive collapse resistance of the studied building by reducing DCR of critical columns by up to 67.0% and reducing the vertical displacements at top of the removed column by up to 81.0% depending on the different column removal cases.